2011
DOI: 10.1139/h11-113
|View full text |Cite
|
Sign up to set email alerts
|

Interval and continuous exercise elicit equivalent postexercise hypotension in prehypertensive men, despite differences in regulation

Abstract: Equicaloric bouts of interval (IE: 5 × 2:2 min at 85% and 40% maximal oxygen uptake) and steady state (SS: 21 min at 60% maximal oxygen uptake) exercise were performed by 13 older prehypertensive males on separate days, at equivalent times of day, to assess the influence of exercise mode on postexercise hypotension (PEH). Exercise conditions were compared with a control session. Cardiovascular measures were collected for 30 min prior to, and 60 min following exercise. PEH, as measured by mean postexercise syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
21

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 48 publications
3
33
0
21
Order By: Relevance
“…Repeated bouts of high-intensity interval exercise (>85 VO 2max ) have been shown to induce similar PEH responses to those obtained with continuous modalities of endurance training performed at lower intensities (∼60 to 65% VO 2max ), both when matched for exercise volume [22], and when compared to lower volume but performed at maximal intensity [23].…”
Section: Benefits Of Hiit For Hypertensionmentioning
confidence: 76%
See 1 more Smart Citation
“…Repeated bouts of high-intensity interval exercise (>85 VO 2max ) have been shown to induce similar PEH responses to those obtained with continuous modalities of endurance training performed at lower intensities (∼60 to 65% VO 2max ), both when matched for exercise volume [22], and when compared to lower volume but performed at maximal intensity [23].…”
Section: Benefits Of Hiit For Hypertensionmentioning
confidence: 76%
“…However, higher intensities elicit exponentially greater increases in sympathetic activity, so it is possible that it may produce higher autonomic adaptations. It has also been suggested that the larger shear stress provided by high-intensity exercise compared to moderate intensity programs further enhances the endothelial function, which plays a major role in the regulation of vasomotor tone and the development of atherosclerosis, and it has also been shown to be a strong predictor of CV risk in hypertensive patients [21][22][23][24][25].…”
Section: Mechanisms Of Benefitsmentioning
confidence: 99%
“…De maneira similar, a HPE tem sido relatada por diversos pesquisadores, entretanto, a maioria, analisa o efeito do exercício físico sobre a PA durante um período de 60 a 120 minutos (BRANDÃO RONDON et al, 2002;CUNHA et al, 2006;LACOMBE et al, 2011;MACDONALD et al, 2002b;MELO et al, 2006;MORAES et al, 2007;PONTES et al, 2008).…”
Section: Instrumentos E Procedimentos De Coleta De Dadosunclassified
“…Considerando-se a PAD, o exercício hipotensor real do exercício foi semelhante em ambas as fases do dia, o que está de acordo com estudos anteriores que também não observaram diferença nas respostas da PAD após o exercício realizado de manhã ou ao final do dia (BISQUOLO et al, 2005;BRITO et al, 2013;CLEROUX et al, 1992;DUJIC et al, 2006;FLORAS et al, 1989;FORJAZ et al, 2004;FORJAZ et al, 1998a;FORJAZ et al, 1999;FORJAZ et al, 1998b;HAGBERG, MONTAIN & MARTIN, 1987;HEADLEY et al, 1998;HEFFERNAN, COLLIER, KELLY, JAE & FERNHALL, 2007;LACOMBE et al, 2011;LEGRAMANTE et al, 2002;LIU et al, 2012;PECANHA, PRODEL, BARTELS, NASARIO-JUNIOR, PAULA, SILVA, LATERZA & LIMA, 2013;RONDON et al, 2002;SANTANA et al, 2013;SENITKO, CHARKOUDIAN & HALLIWILL, 2002;TEIXEIRA et al, 2011).…”
Section: Sessões Controle Exercíciounclassified
“…Por outro lado, realizar o exercício de maneira continua ou intervalada parece não afetar a hipotensão pós-exercício. Lacombe et al (LACOMBE et al, 2011) (FORJAZ et al, 2004;FORJAZ et al, 1998a;MACDONALD, MACDOUGALL & HOGBEN, 1999) e, pelo nosso conhecimento, não há estudos específicos sobre esta problemática em pré-hipertensos. Apesar da controvérsia sobre a melhor intensidade, os estudos realizados pelo nosso grupo que empregaram a intensidade de 50% do VO 2 pico verificaram consistentemente a ocorrência da hipotensão pós-exercício tanto em indivíduos normotensos quanto hipertensos (ARAUJO, 2007;BISQUOLO et al, 2005;FORJAZ et al, 2004;FORJAZ et al, 1998a;FORJAZ et al, 1998b;FORJAZ et al, 2000).…”
unclassified